Analysis of Morphological Traits of Geographically Separated Population of Indigenous Muscovy Duck (Cairina Moschata) - Ogah, D.M. (International Journal of Poultry Science, 2009)
Inter and intra specific variation among muscovy duck ecotypes from three agroecological zones of Nigeria were studied The work evaluate the morphological variation of three ecotypes ( rainforest ecotypes, humid or guinea savanna and dry savanna ecotypes) covering southern or coastal region, central and northern part of Nigeria. Twelve morphological traits including weight were considered. Significant (p<0.05) variation exist within and between ecotypes using population coefficient of variation (ANOVA) bill height had the highest coefficient of variation 79.52 while body length recorded the least variation. There are marked differences in body morphology between sexes in all the ecotypes indicating significant sexual dimorphism. Correlation between the traits were low to high. The inter specific variations in bill structure and body morphology are indication of adaptation to the environment and influence of ecological condition